2021
DOI: 10.21037/apm-21-2481
|View full text |Cite
|
Sign up to set email alerts
|

Application value between dynamic electrocardiogram and MSCT myocardial perfusion imaging in the diagnosis of myocardial ischemia in coronary heart disease

Abstract: Background: Dynamic electrocardiogram and multi-spiral computed tomography (MSCT) myocardial perfusion imaging are commonly used in clinical examination methods, which can provide important reference for the diagnosis of myocardial ischemia in coronary heart disease. To analyze and compare the application value of dynamic electrocardiogram and MSCT myocardial perfusion imaging in the diagnosis of myocardial ischemia in coronary heart disease. Methods: The clinical data of 79 patients diagnosed with coronary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Several studies have evaluated the diagnostic performance of the oxygen pulse using myocardial ischemia detected by myocardial perfusion scan as the diagnostic standard. Belardinelli ( 2 ) showed that ischemia patients diagnosed by Gated- single photon emission computed tomography (SPECT) had a significantly lower peak VO 2 /HR, while Pinkstaff ( 4 ) and Chen ( 5 ) found that the peak VO 2 /HR could not be used to identify patients with myocardial ischemia. This discrepancy could be attributed to the different severities of ischemia in these studies, as oxygen pulse response during incremental exercise might only present with extensive myocardial ischemia ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have evaluated the diagnostic performance of the oxygen pulse using myocardial ischemia detected by myocardial perfusion scan as the diagnostic standard. Belardinelli ( 2 ) showed that ischemia patients diagnosed by Gated- single photon emission computed tomography (SPECT) had a significantly lower peak VO 2 /HR, while Pinkstaff ( 4 ) and Chen ( 5 ) found that the peak VO 2 /HR could not be used to identify patients with myocardial ischemia. This discrepancy could be attributed to the different severities of ischemia in these studies, as oxygen pulse response during incremental exercise might only present with extensive myocardial ischemia ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In theory, the development of myocardial ischemia during exercise may decrease heart stroke volume, and may result in changes in oxygen pulse. Over the past 2 decades, most studies have evaluated the diagnostic performance of oxygen pulse using myocardial ischemia detected by myocardial perfusion scan as the diagnostic standard ( 2 , 4 , 5 ). However, to date, there has been little discussion of the value of oxygen pulse compared to coronary artery anatomy data, and different studies have reported different results.…”
Section: Introductionmentioning
confidence: 99%